169k views
5 votes
Match the numerical expressions to their simplified forms

Match the numerical expressions to their simplified forms-example-1

1 Answer

1 vote

Answer:

4

2

3

1

Explanation:


  • $ (a^x)^{(1)/(y)} = a^(x)/(y) $

  • $ (a^x)/(a^y) = a^(x - y) $

1)
(p^6.q^{{(3)/(2)}})^{{(1)/(3)}}

Therefore,
$ p^{(6)/(3)}.q^{(3)/(2).(1)/(3)} $


$ \implies p^2.q^{(1)/(2)} $

2)
$ (p^5)/(p^(-3)q^(-4)) $


$ = p^5.p^3.q^4 = p^8.q^4 $

Now,
$ (p^8q^4)^{(1)/(4)} $


$ \implies p^{(8)/(4)}.q^{(4)/(4)} $


$ = p^2. q $

3)
$ ((p^2.q^7)/(q^4) )^{(1)/(2) $


$ \implies p^{{(2)/(2)}}.q^{(3)/(2)} $


$ \implies pq^{(3)/(2)} $

4)
$ \frac{(pq^3)^{{(1)/(2)}}}{(pq)^{{(-1)/(2)}}} $


$ \implies p^{{(1)/(2)}}q^{{(3)/(2)}}. p^{{(1)/(2)}}.q^{{(1)/(2)}}} $


$ = pq^2 $

Hence, the answers.

User CBlew
by
6.4k points